Reliability of an electromagnetic tracking system in describing pitching mechanics - Keeley, D. W.; McClary, M. A.; Anguiano-Molina, G.; Oliver, G. D.; Dougherty, C. P.; Torry, M. T. (Sports Technology, 2015)
The availability of various motion capture systems provides researchers and clinicians options in collecting kinematic data. However, with electromagnetic tracking systems, it is imperative to determine the reliability of the system with regard to the specific movement of interest to ensure the collection of data that are reliable, interpretable and may be generalized to a broad spectrum of individuals. Thus, the purpose of this study was to establish the reliability of an electromagnetic tracking device (ETD) in analyzing young baseball pitchers. Two data collection sessions in which throwing kinematics were recorded were conducted across a five-day span. Joint kinematics were calculated using the standards and conventions recommended by the International Shoulder Group. Correlation analyses examining inter-day reliability of the ETD showed that the system was within acceptable limits (R > .73). Throughout the selected instances of the pitch cycle, the ETD used in the current study was shown to be reliable across multiple data collection session with ICCs ranging from R = .73 to R = .86. It appears so long as set-up, sensor attachment and digitization protocols remain consistent across data collection sessions, ETD`s are a reliable tool in analyzing throwing movements in younger participants.